The Influence Of Customer Experience And Customer Trust On Purchase Intention Through Social Commerce On Generation Z In Online Marketplaces - Muhammad Kemal Mumtaz; Donni Junipriansa; Wibowo Wibowo (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study investigates the interrelated effects of customer experience, social commerce, and customer trust on the purchase intentions of Generation Z marketplace consumers in Indonesia. Employing a quantitative research design, empirical data was gathered through a structured online survey distributed to a targeted demographic of Generation Z e-commerce users. The conceptual model was evaluated using PLS-SEM. The analytical results demonstrate that both customer experience and social commerce exert a positive and statistically significant impact on customer trust. Furthermore, the findings reveal that customer trust not only directly drives purchase intention but also serves as a crucial mediating variable that connects the initial user experience and social commerce interactions to final purchasing decisions. The proposed research model exhibits robust explanatory power regarding digital consumer behavior. Ultimately, these findings underscore that cultivating customer trust is a fundamental strategic imperative for amplifying purchase intentions within the contemporary e-commerce landscape.